Female-specific flightless (fsRIDL) phenotype for control of Aedes albopictus. - Geneviève M C Labbé; Sarah Scaife; Siân A Morgan; Zoë H Curtis; Luke Alphey (Public Library of Science (PLoS), 2012)
BACKGROUND: Aedes albopictus, the Asian tiger mosquito, is a vector of several arboviruses including dengue and chikungunya, and is also a significant nuisance mosquito. It is one of the most invasive of mosquitoes with a relentlessly increasing geographic distribution. Conventional control methods have so far failed to control Ae. albopictus adequately. Novel genetics-based strategies offer a promising alternative or aid towards efficient control of this mosquito. METHODOLOGY/PRINCIPAL FINDINGS: We describe here the isolation, characterisation and use of the Ae. albopictus Actin-4 gene to drive a dominant lethal gene in the indirect flight muscles of Ae. albopictus, thus inducing a conditional female-specific late-acting flightless phenotype. We also show that in this context, the Actin-4 regulatory regions from both Ae. albopictus and Ae. aegypti can be used to provide conditional female-specific flightlessness in either species. CONCLUSION/SIGNIFICANCE: With the disease-transmitting females incapacitated, the female flightless phenotype encompasses a genetic sexing mechanism and would be suitable for controlling Ae. albopictus using a male-only release approach as part of an integrated pest management strategy.